The Effect of a Pulmonary Care Bundle Implemented WithCardiac Surgery Patients on Recovery - Yilmaz, Y; Yava, A; Aydin, MS (My University)
Background Various care bundles have been used with cardiac surgery patients in order to improve recovery by reducing complication rates. Pulmonary complications are frequent in cardiac surgery patients. The number of studies examining care bundles aimed at preventing pulmonary complications is limited. Further studies in this field may support the recovery of patients. Aim The primary aim of this study was to examine the effect of a pulmonary care bundle (PCB) on the recovery of patients undergoing cardiac surgery. Study Design In this quasi-experimental study, 103 patients were divided into control and study groups. The control group received standard care. A PCB was administered to the study group by nurses in a Cardiovascular Surgery Clinic in Turkey. The Descriptive Characteristics Data Form, Pulmonary Care Bundle Implementation and Evaluation Form, Respiratory Patterns Follow-up Form and Quality of Recovery Questionnaire-40 were applied to the patients. After data collection, the Quality of Recovery Questionnaire-40 scores and respiratory patterns of the patients in the study and control groups were compared. In addition, the nurses' rate of using the care bundle was examined, and their rate of compliance with the bundle was evaluated. Results The Quality of Recovery Questionnaire-40 scores of the study group (177.70 +/- 10.77) were higher than those of the control group (165.28 +/- 15.63) (p < 0.05). The study group's scores for cough and pathologic pulmonary sound were lower than those of the control group. The oxygen saturation level was higher in the study group than in the control group (p < 0.05). Conclusion The PCB had positive effects on recovery. The respiratory pattern findings were better, and the incidence of respiratory complications was lower in patients who received the care bundle. Relevance to Clinical Practice The PCB supported the patients' recovery. This care bundle can be used to prevent pulmonary complications.
Keywords: cardiac surgery; nursing care; patients' care bundles